2012
DOI: 10.1161/circulationaha.111.084624
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Arterial Grafts Improve Late Survival of Patients Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Background— Use of the left internal mammary artery (LIMA) in multivessel coronary artery disease improves survival after coronary artery bypass graft surgery; however, the survival benefit of multiple arterial (MultArt) grafts is debated. Methods and Results— We reviewed 8622 Mayo Clinic patients who had isolated primary coronary artery bypass graft surgery for multivessel coronary artery disease from 1993 to 2009. Patients were stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(147 citation statements)
references
References 28 publications
9
135
0
3
Order By: Relevance
“…Moreover, the relatively small sample size can partially account for lack of survival benefit by using the RA. However, the non-significant trend towards lower survival probabilities in the BITA+RA group, also reported by others [4,5] limits the potential role of type beta error in rejecting the hypothesis of the superiority of the RA. Finally, the study was observational on prospectively collected data and selection bias cannot be excluded despite propensity score adjustment.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, the relatively small sample size can partially account for lack of survival benefit by using the RA. However, the non-significant trend towards lower survival probabilities in the BITA+RA group, also reported by others [4,5] limits the potential role of type beta error in rejecting the hypothesis of the superiority of the RA. Finally, the study was observational on prospectively collected data and selection bias cannot be excluded despite propensity score adjustment.…”
Section: Discussionmentioning
confidence: 66%
“…The right internal thoracic artery (RITA) has been advocated to further improve long term revascularization outcomes [2]. Whether the use of the radial artery (RA) [3][4][5] as third arterial conduit in addition to bilateral internal thoracic artery (BITA) grafting is associated with better survival when compared to BITA plus saphenous vein (SV) remains to be determined with isolated small series reporting conflicting results [6,7].…”
mentioning
confidence: 99%
“…This study has the limitation of a 30 days post-intervention follow up and the finding of an higher rate of wound infection is not reported in other propensity matched studies [2,22,24,25].…”
Section: The Bilateral Internal Mammary Arterymentioning
confidence: 71%
“…LITA and RITA have been used as peduncolated or skeletonized graft, with direct anastomosis on the target vessels or in composite grafts (Y graft), used to perform the revascularization of a single coronary branch or more coronary branches [19,21] [2,[19][20][21][22].…”
Section: The Bilateral Internal Mammary Arterymentioning
confidence: 99%
“…Reports on diagnostic accuracy of MDCT in CABG have shown values of sensitivity and specificity over 95% for the presence of lesions in these vessels. However, the investigation of native vessels showed that sensitivity and specificity are significantly lower than in patients with suspected coronary artery disease [14][15][16][17][18].…”
Section: Accuracy Of Different Generations Of Ct In Coronary Bypass Gmentioning
confidence: 98%